2013
DOI: 10.1089/cap.2012.0073
|View full text |Cite
|
Sign up to set email alerts
|

NWP06, an Extended-Release Oral Suspension of Methylphenidate, Improved Attention-Deficit/Hyperactivity Disorder Symptoms Compared with Placebo in a Laboratory Classroom Study

Abstract: ClinicalTrials.gov Identifier: NCT00904670. http://www.clinicaltrials.gov/ct2/show/NCT00904670 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 19 publications
6
54
0
1
Order By: Relevance
“…The onset of action of Quillivant XR ® was demonstrated at 45 minutes in the study, the first time point measured. 34 While Quillivant XR ® has been shown efficacious for a duration of 12 hours in studies against placebo, future trials need to be conducted comparing it to other available extended-release methylphenidate formulations. 34 Since Quillivant XR ® is an oral suspension, it could become the preferred methylphenidate product in children with ADHD with difficulty swallowing.…”
Section: Methylphenidate Extended-release Oral Liquidmentioning
confidence: 99%
“…The onset of action of Quillivant XR ® was demonstrated at 45 minutes in the study, the first time point measured. 34 While Quillivant XR ® has been shown efficacious for a duration of 12 hours in studies against placebo, future trials need to be conducted comparing it to other available extended-release methylphenidate formulations. 34 Since Quillivant XR ® is an oral suspension, it could become the preferred methylphenidate product in children with ADHD with difficulty swallowing.…”
Section: Methylphenidate Extended-release Oral Liquidmentioning
confidence: 99%
“…They concluded that methylphenidate hydrochloride treatment effectively reduced symptoms of ADHD in children beginning at 45 minutes and continuing for 12 hours post-dose. Methylphenidate hydrochloride was also shown to be well tolerated in the study (Wigal et al, 2013).…”
Section: Newer Stimulant Formulationsmentioning
confidence: 90%
“…The study, though focused on singledose pharmacokinetics and limited to a small sample size, demonstrated that methylphenidate hydrochloride had a pharmacokinetic profile similar to other extended-release preparations and was safe and well tolerated by children aged 9-15 years with ADHD. Wigal and colleagues conducted an 8-week, dose-optimized, randomized, double-blind, placebo-controlled, crossover laboratory school study of methylphenidate hydrochloride in 45 children ages 6-12 years (Wigal, Childress, Belden, & Berry, 2013). Methylphenidate hydrochloride resulted in significant (p < 0.0001) improvements in the Swanson, Kotkin, Agler, M-Flynn and Pelham Rating scale (SKAMP)-Combined score at four hours post-dose as compared with placebo in the 39 completers and significant separation from placebo occurred at each time point tested (0.75, 2, 4, 8, 10, 12 hours) (Findling, 2008).…”
Section: Newer Stimulant Formulationsmentioning
confidence: 99%
“…MEROS is supplied as a powder that is reconstituted with water by the pharmacist prior to dispensing. On reconstitution, MEROS forms an extended‐release oral suspension of methylphenidate, available in a 25 mg per 5 mL (5 mg/mL) concentration and intended for once‐daily oral administration . According to the label, for patients ages 6 years and above, the recommended starting dose is 20 mg given orally once daily in the morning.…”
mentioning
confidence: 99%
“…The formulation contains approximately 20% immediate‐release and 80% extended‐release methylphenidate. MEROS has demonstrated onset of action in 45 minutes and duration of action through 12 hours postdosing . The relative bioavailability of 60 mg of MEROS compared with 60 mg of immediate‐release methylphenidate hydrochloride (HCl) oral solution (given as 2 30‐mg doses 6 hours apart) is 95% …”
mentioning
confidence: 99%